Analisis Keterampilan Beripikir Kritis Siswa Pada Materi Sistem Pertahanan Tubuh Melalui Pembelajaran Model TGT - Aini Khairunnisa; Tuti Kurniati; Hadiansah Hadiansah (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2023)
In the 21st Century learning, it requires students to develop the 4Cs, one of which is thinking. Classroom learning is needed where students are motivated in learning activities so that they are actively involved and bring up critical thinking. To achieve these demands, the Teams Games Tournament learning model has the opportunity to be able to make students actively involved and the same time practice their critical thinking skills. The purpose of this study is to analyze the effect and describe the response to the Teams games Tournament learning model assisted by the Truth or dare media on critical thinking skills in the body's defense system. This research was conducted in one of the senior high schools in Baleendah with a quantitative approach. The time of research was carried out in the 2021/2022 academic year. The sample that uses this model is class XI IPA 2, totaling 35 people. This research instrument uses test questions for influence analysis and questionnaires to determine student responses. Based on the results of the study, it is known that there is an increase in critical thinking, the N-Gain value of 0.375 with the medium category of responses and student responses getting an average value of 79%, which means it has a strong interpretation. It can be conclud that through learning the Teams Games Tournament model is assisted by Truth or dare media and there is an increase in critical thinking on the material of the body's defense system and has a very good student response.